2014
DOI: 10.1016/j.acra.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Breast DCE-MRI

Abstract: Rationale and Objectives Breast dynamic contrast enhanced (DCE) MRI scanning protocols vary widely. The purpose of this study was to determine the effects of post-contrast timing on delayed-phase lesion kinetics assessment and ability to discriminate malignant from benign lesions. Materials and Methods Following IRB approval, we retrospectively reviewed all lesions assessed on MR examinations from 4/2005 to 6/2006. DCE-MRI was performed with 90 seconds temporal resolution. Delayed-phase kinetic parameters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…However, Grimm et al ( 37 ) found that the addition of the second post-contrast series for lesion kinetic analysis did not affect reader sensitivity or specificity. This may be in accordance with previous work which indicated that fewer post-contrast sequences may not significantly impact diagnostic accuracy ( 46 ).…”
Section: Considerationssupporting
confidence: 93%
“…However, Grimm et al ( 37 ) found that the addition of the second post-contrast series for lesion kinetic analysis did not affect reader sensitivity or specificity. This may be in accordance with previous work which indicated that fewer post-contrast sequences may not significantly impact diagnostic accuracy ( 46 ).…”
Section: Considerationssupporting
confidence: 93%
“…Kul et al [29] found that the effectiveness of DWI using ADC mean was lower for NME lesions as compared with masses and that the difference between the ADCs of benign and malignant lesions was smaller for NME lesions. Partridge et al [30] reported that although DWI using a Wtu measurement approach and ADC mean is a promising tool for differential diagnosis for both masses and NME lesions, ADC measurements may be more useful for discriminating benign from malignant in masses than for discriminating lesions with NME enhancement. Recently, studies have investigated intravoxel incoherent motion and quantitative non-gaussian diffusion MRI [3133].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the size of the vessels that can be resolved is (of course) intimately connected to the spatial resolution and signal-to-noise of the images themselves. Because the breast vasculature was segmented on images with a voxel size of (0.8 mm), 3 vessels with radii much smaller than 0.8 mm cannot be directly segmented. We attempted to overcome this limitation by applying a cost-based search to track possible paths connecting segmented vessels and the lesions, but this estimate cannot be directly validated with our current data set.…”
Section: Discussionmentioning
confidence: 99%
“…DCE-MRI involves the serial acquisition of heavily T 1weighted images acquired before, during, and after the injection of a paramagnetic contrast agent. 1 Both semi-quantitative and quantitative analysis of DCE-MRI have been shown to provide important insights in both the diagnostic [2][3][4] and prognostic [5][6][7] settings for breast cancer. Within the diagnostic setting, the sensitivity of DCE-MRI has been reported as 88% to 100% 8,9 but with a variable specificity of 63% to 96%.…”
Section: Introductionmentioning
confidence: 99%